Art insight : understanding art and why it matters - Silberstein, Fanchon Jean (Intellect, 2020)
A first encounter with art is like meeting a stranger: it opens you to new ideas, people, places, and parts of yourself. In Art inSight: Conversations with Cultures, Fanchon Silberstein delves into the first known art and explores what it can reveal about how its makers saw the world and how contemporary artists can help us to see our own. The result is equal parts an ode to the joy of artful engagement, a how-to for anyone interested in understanding art and culture, and a journey around the world from prehistory to the present day. Readers confront strangeness through observation, description, and conversation, and are given the skills to understand cross-cultural divisions and perceive diverse ways of interpreting the world. Organized by ideas rather than history, chronology, or cultures, the book presents dialogues, imagining interactions between paintings created centuries apart, and describing discussions among students learning the role of art in conflict resolution. By emphasizing the relationship between viewer and image, Art inSight urges readers to discover meaning in their own ways and offers questions that lead them into profound connections with works of art and the cultures behind them.